2002
DOI: 10.1139/g01-144
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced molecular marker based genetic map of perennial ryegrass (Lolium perenne) reveals comparative relationships with other Poaceae genomes

Abstract: A molecular-marker linkage map has been constructed for perennial ryegrass (Lolium perenne L.) using a one-way pseudo-testcross population based on the mating of a multiple heterozygous individual with a doubled haploid genotype. RFLP, AFLP, isoenzyme, and EST data from four collaborating laboratories within the International Lolium Genome Initiative were combined to produce an integrated genetic map containing 240 loci covering 811 cM on seven linkage groups. The map contained 124 codominant markers, of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
238
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(264 citation statements)
references
References 53 publications
23
238
2
Order By: Relevance
“…Lolium/Festuca and rice is largely consistent with previous report (Jones et al 2002;Alm et al 2003;Sim et al 2005). For example, with a few exceptions, rice chromosome 1 corresponds to Lolium/Festuca chromosome 3 , and rice chromosome 3 corresponds to Lolium/Festuca chromosome 4 (Tables 1 and 2).…”
Section: Species Specificities Of the Markers Within Combinations Of supporting
confidence: 91%
See 1 more Smart Citation
“…Lolium/Festuca and rice is largely consistent with previous report (Jones et al 2002;Alm et al 2003;Sim et al 2005). For example, with a few exceptions, rice chromosome 1 corresponds to Lolium/Festuca chromosome 3 , and rice chromosome 3 corresponds to Lolium/Festuca chromosome 4 (Tables 1 and 2).…”
Section: Species Specificities Of the Markers Within Combinations Of supporting
confidence: 91%
“…Out of 143 intron-flanking EST markers, 107 (74.8%) markers were assigned to one of the 7 Festuca chromosomes (Tables 2 and 3 Lolium/Festuca and rice revealed several syntenic segments largely in agreement with previous reports (Jones et al 2002;Alm et al 2003;Sim et al 2005;King et al 2007). …”
Section: Chromosome Mapping Of Intron-flanking Est Markerssupporting
confidence: 88%
“…As a member of the Poaceae clade in the grass phylogeny, orchardgrass has a base chromosome number of seven. Several studies have shown the synteny between rice and the seven-chromosome grass species (Gale and Devos 1998; LaRota and Sorrells 2004; Jones et al 2002a). Within orchardgrass, synteny to other grasses may allow for targeted mapping and association studies.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative mapping was performed as described by Jones et al (2002b). The comparative location of probes in the Triticeae and rice genomes were as reported by Jones et al (2002b) and/or ascertained using the Graingenes (http:/ / grain.jouy.inra.fr/ggpages/) and Gramene (http:/ /www.…”
Section: Comparative Analysismentioning
confidence: 99%
“…In our study, QTL1 is also located on LG2, in the proximity of Xcdo385 (Figure 3). According to Jones et al (2002b), Xcdo385 maps to LG2 in the ILGI mapping population. It is in this genomic region that Dumsday et al (2003) also located SSR markers associated with crown rust resistance.…”
Section: H Muylle Et Almentioning
confidence: 99%